Arbitrators and the Duty of Disclosure in the Public Procurement Law and its Regulations - Castillo Freyre, Mario (2015)
The requirements that have to be complied by the other arbitrators in the arbitration procedures referred to contracts with the State are developed in the first section of this article. Emphasis is placed on the matter referred to the expertise that should have the Single Arbitrators, as well as the Chairman of the Arbitral Court.Afterwards, it is also analyzed the scope of the duty of disclosure of arbitrators and their obligation to remain –during the whole development of the arbitration procedure– independent and impartial, without keeping personal, professional or business relationships with the parties involved. All through the entire article, reference is also made to how such matters are ruled in the new Law on Contracts with the State, Law N° 30225, which has not become in force yet.